Modeling of the As (III) adsorption using Fe impregnated polyethylene terephthalate char matrix: A statistical approach - Sawood G.M.; Gautam S.B.; Mishra A.; Dixit S.; Singh N. (My University, 2025)
The present research aimed to analyse the impact of economical Fe impregnated polyethylene terephthalate (PET) char (PETC-Fe) for adsorption of As (III) through series of column experiments. For an inlet arsenite concentration of 1,000 μg/L, PETC-Fe exhibits excellent uptake capacity of 1,892 μg/g. Central composite design (CCD) in response surface methodology (RSM) was used to evaluate the influence of various process variables on the response function (breakthrough time) for optimization and assessment of interaction effects. The breakthrough time is more responsive to influent As (III) concentration and bed height than inlet flow rate, according to the perturbation plot. Adams-Bohart, Bed Depth Service Time (BDST) model, and Thomas models were used to model the dynamics of the adsorption system. The BDST model suited the experimental data well in the early part of the breakthrough curve, but there were minor variations over the breakpoints. Despite the fact that the experimental values and the data sets estimated using the Adams-Bohart model followed a similar pattern, they differed slightly. The PETC-Fe was found to be a sustainable and highly economical adsorbent, with a desorption performance of more than 97%, indicating the adsorbent's reusability. This adsorbent's excellent As (III) uptake capacity and regeneration performance imply that it might be used in industrial/domestic applications, and the information obtained could aid in future scaling up of the adsorption system. © 2022 IWA Publishing. All rights reserved.